Pengaruh Brand Awareness terhadap Keputusan Pembelian pada PT Gramedia Asri Media Cabang Cinere Mall Depok - Wiwin Wianti; Wangsit Supeno; Ira Karina Putri (Jurnal Ekonomi, 2019)
Gramedia Asri Media is a company that specializes in retail that offers best books from various publishers , as well as school supplies products and an office that is best quality. PT Gramedia Asri Media trying continue to create a the brand awareness to public, In order to become the dominant choice in their purchasing choices. The study be conducted for determine how big influence the brand awareness of purchasing decisions. The method of this study used by quantitative method with Independent variables are Brand Awareness and the dependent variabel is purchasing decision and with sample of 30 respondents. The sampling technique used in this study is Sample Random Sampling. The method of this study used by methods observation, methods interview, methods questionnaire, and atudy documentation. Methods of data analysis used in this correlation coefficient analysis methods, determination coefficient, and simple linear regression analysis. Data processing was performed by using SPSS 23 software for Windows. Through the test R brand awareness has a strong relationship to the purchase decision. The influence of brand awareness on purchasing decision is 60,9% and the rest is 39,09% influenced by other factors not examines like brand image, promotion, quality of service and others. Each increase of one scala Brand Awareness will raise the Purchase Decision by 0,804.